CURRENT EPIZOOTIC SITUATION AND FORECAST FOR 2015 ABOUT MAIN HELMINTHOSIS IN ANIMALS ON THE TERRITORY OF RUSSIA - V. V. Gorokhov; N. A. Samoylovskaya; A. V. Uspensky; I. F. Klenova; R. A. Peshkov; E. V. Puzanova; A. S. Moskvin (Российский паразитологический журнал, 2016)
The epizootic situation on main animal helminthosis which we have observed in Russian Federation in the period from 1990 to 2014 allows us to come to the conclusion that the development of epizootic process is affected by ecological components such as: conditions of pastures and water reservoirs, weather and climate especially in current pasture season; therefore it is necessary to conduct the antiparasitic treatment.